Output enhanced compact multilayer flexible nanogenerator for self-powered wireless remote system. Issue 25 (19th June 2017) - Wu, Nan; Jiang, Hulin; Li, Wenbo; Lin, Shizhe; Zhong, Junwen; Yuan, Fang; Huang, Liang; Hu, Bin; Zhou, Jun
Abstract : A simple-structured compact multilayer flexible nanogenerator was demonstrated in this work. The power density of the nanogenerator could be optimized by structural controlling. This strategy may pave a new way for self-powered electronic systems. Abstract : Flexible electret nanogenerators that can convert mechanical energy into electricity have received intensive attention in recent years. However, drawbacks of low outputs and impedance mismatch with traditional electronics limit their extensive applications. In this work, we propose a novel method to enhance outputs by optimizing device structure of a compact multilayer flexible nanogenerator (CMFN). Meanwhile, load resistance corresponding to maximum output power can be reduced to alleviate impedance mismatching. By pressing a 4 × 4 cm 2 CMFN with a height of 2 mm, peak output current was reached at ∼3 mA, which was large enough to power a wireless remote system with an effective emitting distance of 30 cm. This study successfully demonstrates a simple and efficient strategy to fabricate flexible electrostatic nanogenerators with outstanding output properties, and promotes progress of self-powered electronics.